Redefining Japaneseness : Japanese Americans in the ancestral homeland - Yamashiro, Jane H. (Asian American studies today., 2017)
"How does the experience of living in Japan to study and work affect how Japanese Americans see themselves? Constructing Japanese American Identity in Japan examines how daily interactions with Japanese in Japan shape how Japanese Americans think about their own Japanese backgrounds. Based on interviews and ethnographic fieldwork in the Tokyo area, Yamashiro aptly demonstrates how as U.S. citizens of Japanese ancestry, Japanese Americans navigate and complicate the mainstream categories of 'Japanese' and 'foreigner' in Japan. By using a transnational framework, Yamashiro reveals how Japanese American migrants in Japan are influenced by not only Japanese social norms and expectations, but the U.S.-based categories and notions of race that they bring with them, as well. Considering factors such as phenotype, language, usage of Japanese names, and differences between Japanese Americans from the U.S. continent and Hawai'i, Yamashiro reveals how the diversity of Japanese American experiences in Japan reflects their diverse demographics, histories, and experiences in the United States. In addition, the book details generational, gendered factors in how, after returning to the United States, Japanese Americans reflect on their experiences in Japan"--Provided by publisher